Parliamentary Debate on Dilma Rousseff’s Impeachment: The Words of Brazilian Women Senators - Antonio Teixeira de Barros; Myriam Violeta Cavalhero (Colombia Internacional, 2024)
Objective/context: The study aimed to analyze the debate among Brazilian women senators during the impeachment trial of Dilma Rousseff in 2016. Methodology: Elements of discourse analysis were applied to investigate the main question: How did the debate develop among women senators, considering the ideological spectrum of the party and their position on the impediment (favorable or contrary)? The analysis presents a political-ideological profile of women senators, the arguments used by them in the debate, and the different uses of the defense of democracy. Conclusions: The left-wing women senators were more diligent and repeated their arguments more frequently to increase their discursive visibility. They also addressed the non-existence of a crime of responsibility, a condition to initiate an impeachment process. Women senators from the right and the center, on the other hand, resorted to rhetorical models to reiterate that the then-president of the Republic was no longer in a position to maintain a parliamentary base to support her government. The senators of this group also stated that the investigations demonstrated the use of schemes to irresponsibly disguise public accounts, exclusively with a view to Rousseff's reelection. Originality: It is relevant to highlight the original fact that this is an analysis of the impediment of a woman in the office of President of the Republic from the female perspective of the parliamentary body of the Senate, the institution in charge of judging the impeachment process.